2016
DOI: 10.1123/jpah.2015-0343
|View full text |Cite
|
Sign up to set email alerts
|

Use of Social Networking Sites and Adherence to Physical Activity and Screen Time Recommendations in Adolescents

Abstract: Heavy use of SNSs has a negative influence on the adherence to the ST recommendation in both males and females; however, infrequent use of SNSs was related to the adherence to the PA recommendation and concurrent adherence to both recommendations in males only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The emergence of screen media as a predominant activity in the lives of adolescents is posited as one such risk. The research is unequivocal that adolescence is a period of high screen media use, and mobile devices now allow young people to be constantly connected to multiple activities, often simultaneously (Houghton et al 2015 ; Sampasa-Kanyinga and Chaput 2016 ). This increased accessibility and time spent engaged with electronic screen media on a daily basis has raised health related concerns (see American Academy of Pediatrics AAP.…”
Section: Introductionmentioning
confidence: 99%
“…The emergence of screen media as a predominant activity in the lives of adolescents is posited as one such risk. The research is unequivocal that adolescence is a period of high screen media use, and mobile devices now allow young people to be constantly connected to multiple activities, often simultaneously (Houghton et al 2015 ; Sampasa-Kanyinga and Chaput 2016 ). This increased accessibility and time spent engaged with electronic screen media on a daily basis has raised health related concerns (see American Academy of Pediatrics AAP.…”
Section: Introductionmentioning
confidence: 99%
“…Although sedentary behaviour has been largely overlooked in studies of monetary gambling behaviours in general, some existing evidence suggests that more substantial periods of inactivity as well as indicators of poor physical health, such as obesity, are positively associated with a propensity toward monetary gambling across all age groups [ 45 , 46 ]. Additionally, it has been shown that sedentary behaviour is particularly prominent during adolescence, with Canadian adolescents typically spending over 8 h daily engaging in sedentary activities, primarily those involving screens [ 47 – 49 ]. Although a pervasiveness in screen time is harmful on its own [ 50 ], it may also increase exposure to online gaming and gambling, and may subsequently result in greater SCG play among this cohort.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of such activities include parent–child interactions, book reading, physical activity, and regular sleep (Xiang et al, 2020). Children frequently using online technologies display poorer social skills (Downey & Gibbs, 2020) and are less likely to meet recommended levels of physical activity (Sampasa‐Kanyinga & Chaput, 2016) or sleep (LeBourgeois et al, 2017; Pearson, Sherar, & Hamer, 2019). Frequent screen time at age 11 predicts more sedentary behaviors (Pearson et al, 2019) and greater body mass index at age 14 (Engberg, Figueiredo, Rounge, Weiderpass, & Viljakainen, 2019).…”
Section: Potential Harms and Benefits Of Frequent Electronic Device Umentioning
confidence: 99%
“…Consistent with the displacement hypothesis, frequent screen time is associated with cognitive and behavioral delays (Madigan, Browne, Racine, Mori, & Tough, 2019; McNamee, Mendolia, & Yerokhin, 2019), academic difficulties (Adelantado‐Renau et al, 2019; Mundy et al, 2020), lower levels of emotional well‐being and greater anxiety, emotional instability, self‐harm, depression and suicidal ideation (e.g., Barthorpe, Winstone, Mars, & Moran, 2020; Twenge & Campbell, 2019), comorbid internalizing and externalizing problem behaviors (Riehm et al, 2019), lower self‐value (McNamee et al, 2019), increased risk for attention deficit hyperactivity disorder‐related behaviors (George et al, 2018; Ra et al, 2018), and poorer perceived quality of life (Stiglic & Viner, 2019) in analyses adjusted for possible confounds. Negative associations between children’s frequency of being online and their cognitive, academic, behavioral, and physical development are evident after more than 1 hr of daily use (Mundy et al, 2020; Sampasa‐Kanyinga & Chaput, 2016; Sampasa‐Kanyinga, Chaput, & Hamilton, 2019; Twenge & Campbell, 2019). Frequent use of online technologies is also associated with substance use, risky sexual behaviors, problematic gambling, and cyberbullying (e.g., Kaur, Rutherford, Martins, & Keyes, 2020; Vannucci, Simpson, Gagnon, & Mccauley, 2020).…”
Section: Potential Harms and Benefits Of Frequent Electronic Device Umentioning
confidence: 99%